Sult og ensomhed er kilden til min skrift – en forelæsning på Stanford Universitet - Yan, Mo (Passage - Tidsskrift for litteratur og kritik, 2013)
Mo Yan: “Hunger and Loneliness: My Muses” Mo Yan’s text is a Danish translation of a lecture in Chinese that he gave at Stanford University in 2000.